MOSAIK: A Formal Model for Self-Organizing Manufacturing Systems - Charpenay, Victor; Schraudner, Daniel; Seidelmann, Thomas; Spieldenner, Torsten; Weise, Jens; Schubotz, Rene; Mostaghim, Sanaz; Harth, Andreas (IEEE Pervasive Computing, 2020)
In this article, we review past and current system architectures displaying self-organization in the domain of manufacturing. Based on a corpus of 84 reference papers, we find that multiagent systems (MAS) play a significant role in self-organization, especially MAS featuring bio-inspired algorithms for agent coordination. The emergence of new classes of cyber-physical systems further strengthens the prevalence of MAS on the subject. As outcome of our review, we devise the MOSAIK model, a generic model synthesizing all system architectures found in our corpus. The MOSAIK model can be used as a reference for formally comparing distinct architectures. We also use it to identify gaps for future research on self-organizing manufacturing systems. The model includes the central concepts of Agent and Artifact, which suggest that the Web is an adequate communication infrastructure for modern manufacturing systems: Agents become (autonomous) Web Agents and Artifacts become resources exposed by Web servers.
Created from Fastlane, Scopus look-up
Keywords: Biological system modeling; Complexity theory; Computer architecture; Manufacturing; Optimization; Unified modeling language; Workstations